1996
DOI: 10.1111/j.1745-4506.1996.tb00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of Foodservice Directors After Implementation of a Conventional or Cook-Chill Foodservice System1

Abstract: The objectives of this study were to compare foodservice directors’ratings of satisfaction with conventional or cook‐chill systems and to determine whether these ratings differed based on the type of system. A total of 126 foodservice directors (51 % response) rated 42 issues related to the foodservice system they had chosen. Results indicated that foodservice directors were at least somewhat satisfied with all issues. Highest ratings were given for foodservice staff acceptance, total food cost, and hospital a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…There has been a considerable amount of research on the impact of cook‐chill food service on the nutritional quality in hospital food (Williams, 1996) and service satisfaction (Nettles & Gregoire, 1996). However, there has been little attention to the more subtle impacts the system may have on the choices of food provided on the menu.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a considerable amount of research on the impact of cook‐chill food service on the nutritional quality in hospital food (Williams, 1996) and service satisfaction (Nettles & Gregoire, 1996). However, there has been little attention to the more subtle impacts the system may have on the choices of food provided on the menu.…”
Section: Discussionmentioning
confidence: 99%
“…This comment may also reflect frustration about a lack of control that many food service managers feel regarding decisions to introduce new catering technologies such as cook‐chill, which are often driven by senior hospital managers who are solely concerned with economic considerations. A US survey of 126 food service directors that found that managers of cook‐chill systems reported lower production costs but also lower patient satisfaction, compared to directors of conventional food services (Nettles & Gregoire 1996). King (1991) also reported a 71% favourable score for patient satisfaction with the cook‐fresh systems compared to only 50% with the cook‐chill systems.…”
Section: Discussionmentioning
confidence: 99%
“…Many hospital foodservice production systems exist, including cook-fresh, cook-freeze and cookchill. The principal foodservice models in Australia are cook-chill and cook-freeze systems where food is preprepared and then rethermalised at required times (Greathouse et al 1989;McLelland & Williams 2003;Nettles & Gregoire 2006) and the traditional cook-fresh model. Other foodservice models, such as 'Steamplicity' whereby meals are plated in a central production unit prior to distribution to hospitals, then microwaved at short notice prior to meal times, have been implemented with success in the UK (Edwards & Hartwell 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Other foodservice models, such as 'Steamplicity' whereby meals are plated in a central production unit prior to distribution to hospitals, then microwaved at short notice prior to meal times, have been implemented with success in the UK (Edwards & Hartwell 2006). The principal foodservice models in Australia are cook-chill and cook-freeze systems where food is preprepared and then rethermalised at required times (Greathouse et al 1989;McLelland & Williams 2003;Nettles & Gregoire 2006) and the traditional cook-fresh model. The Department of Human Services in Victoria are moving food production to central production kitchens for many Victorian hospitals, an approach being used elsewhere (Silverman et al 2000).…”
Section: Introductionmentioning
confidence: 99%